“Shining a Light” on Mature-Aged Students In, and From, Regional and Remote Australia - Crawford, Nicole; Emery, Sherridan (Queensland University of Technology, 2021)
This article shines a light on a little-known cohort of higher education participants, mature-aged students in, and from, regional and remote Australia – the focus of a National Centre for Student Equity in Higher Education mixed-methods study. Notable patterns were found in the quantitative data; for instance, compared to their metropolitan counterparts, higher proportions of regional and remote students were older, female, from low socio-economic status areas, Aboriginal and Torres Strait Islander, and studied online and/or part-time. The presentation of four vignettes from the interviews uncovers the stories behind the numbers, revealing students’ diverse and complex circumstances; two of the students shared experiences of facing systemic obstacles, while the other two described receiving invaluable institutional support. The obstacles can be attributed to systems designed for “ideal”, “implied” and “traditional” students, and entrenched attitudes that privilege some “types” of students over others and limit the aim of full participation for all students.